ECONOMIC CALCULATION AND SENSITIVITY ANALYSIS FOR MARGINAL WELL IN THE UNITED STATES - Maulana Firdauz, Reza
This study evaluates the economic feasibility and sensitivity of marginal wells in the United States, focusing on the Riser A-1 well in Texas. The Riser A-1 well was chosen as it represents typical unconventional gas wells in the USA, mostly categorized as marginal wells. Utilizing decline curve analysis with Duong’s model, the study forecasts production and applies discounted cash flow analysis to calculate net present value (NPV) over time. Sensitivity analysis highlights critical factors impacting profitability, including production rates, gas prices, and lease operating expenses (LOE). The research reveals that marginal wells, despite lower production levels, can remain economically viable with effective management of LOE and market conditions. Recommendations include conducting comparative analyses with similar wells in Indonesia to enhance strategies for developing unconventional resources and maximizing economic returns.